A Model for Optimizing Tahsinul Qira’ah (Quranic Recitation Improvement) through a Quranic Reading Assessment Program Using the Talaqqi Method at Pondok Jannatun Naim, Lampung - Muhammad Fajar; Agus Pahrudin; Achi Rinaldi; Ali Murtadho (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to develop an optimization model for tahsinul qiro’ah (Qur’anic reading improvement) through a Qur’anic reading mapping program integrated with the talaqqi method at Pondok Jannatun Naim Lampung. Specifically, the study analyzes the initial condition of students’ reading abilities, describes the design and implementation of the reading mapping program combined with talaqqi, identifies supporting and inhibiting factors, and evaluates the effectiveness of the model. The research employs a qualitative descriptive-analytical approach conducted at Pondok Jannatun Naim Lampung involving seventh-grade students. Data collection techniques include participatory observation, in-depth interviews with caregivers, teachers, and students, and documentation analysis. Data analysis follows the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing/verification. Initial findings from the pre-mapping evaluation using a reading checklist for 17 seventh-grade students indicate diverse reading proficiency levels, with most students showing notes such as “less fluent”, “needs improvement”, and “still lacking in tajwid application”. These findings highlight the necessity of a systematic and targeted learning strategy. The proposed model integrates diagnostic reading mapping as a basis for individualized talaqqi instruction, enabling teachers to monitor student progress accurately and provide tailored guidance. This research contributes a novel conceptual model for optimizing Qur’anic reading instruction in modern Islamic boarding schools by combining traditional talaqqi with systematic evaluation tools.